The Legitimacy of Hawalah Contract in Cash on Delivery Payment System (Qiyas Analysis in Online Sale Transactions) - Airin Nur Abidah; Muhammad Zainuddin Sunarto (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2026)
This study examines the legitimacy of the Cash on Delivery (COD) payment system in online sale transactions through the application of qiyas by analogizing COD to the hawalah contract. This normative legal research employs the al-sabr wa al-taqsim method within the framework of masalik al-‘illah to determine the effective legal cause (‘illat) underlying the permissibility of COD. The analysis demonstrates that the transfer of payment obligation (naql al-dayn) constitutes the sole ‘illat mu‘tabarah that unites COD with hawalah. Unlike bai‘ al-dayn bi al-dayn, which involves the exchange of debt for debt and is prohibited in Islamic law, COD operates as a mechanism for transferring the collection of payment through a third party. Accordingly, COD is deemed legally valid (mubah) under Islamic law as a payment system facilitated by a third party and does not fall within the prohibition of bai‘ al-dayn bi al-dayn. This finding affirms the methodological flexibility of Islamic commercial jurisprudence in addressing contemporary digital transactions while maintaining normative consistency with classical legal principles.